Philosophy feminism - Hay, Carol 1977- (Macmillan interdisciplinary handbooks, 2017)
"Covers such topics as the three waves of feminism, sexism and oppression, intersectionality, disability, race, LGBTQ theory, and ecofeminism. The use of film, literature, art, case studies, and other disciplines or situations/events provide illustrations of human experiences which work as gateways to questions philosophers try to address"...